Microhabitat associations of vascular epiphytes in a wet tropical forest canopy. (19th January 2015) - Woods, Carrie L.; Cardelús, Catherine L.; DeWalt, Saara J.; Piper, Frida
Summary In tropical forests, vascular epiphyte diversity increases with tree size, which could result from an increase in area, time for colonization or an increase in microhabitat heterogeneity within‐tree crowns if vascular epiphyte species are specialized to particular microhabitats within the crown. The importance of microhabitats in structuring epiphyte communities has been hypothesized for more than 120 years but not yet confirmed. We tested the importance of microhabitats in structuring epiphyte communities by examining microhabitat heterogeneity and epiphyte communities within the crowns of different‐sized Virola koschnyi (Myristicaceae) emergent trees in a Costa Rican tropical wet forest. We tested the degree to which epiphyte species composition was associated with environmental conditions and resources (i.e. microhabitats) using multivariate analyses and a null model that compared the observed epiphyte assemblages amongst different‐sized trees and crown zones with assemblages generated randomly. This study is the first to rigorously examine the degree of microhabitat specialization in epiphyte communities. Microhabitat heterogeneity, epiphyte species richness and abundance increased with tree size. The largest trees had the highest microhabitat and epiphyte diversity and a unique inner crown microhabitat with canopy humus. The few epiphytes found on small trees were mostly bark ferns. Large trees had different epiphyte communities in different parts of the crown; the inner crown contained species not abundant in any other microhabitat (i.e. aroids, cyclanths and humus ferns), and the outer crown contained bark ferns and atmospheric bromeliads. Variation in species composition amongst tree size classes was significantly related to the mean daily maximum vapour pressure deficit and tree diameter, while variation within large tree crowns was significantly related to canopy humus cover. Microhabitat specialization of epiphyte species increased with tree size with 6% of species significantly associated with small trees and 57% significantly associated with large trees. Of the species present in large tree crowns, 23% were specialized to the unique inner crown microhabitat. Synthesis. The increase in microhabitat heterogeneity within tree crowns as trees grow contributes to changes in epiphyte community structure, which supports decades‐old hypotheses of the importance of microhabitat diversity and specialization in structuring tropical epiphyte communities.